Establishing and comparing electrical energy consumption of sawmills. (11th February 2020) - Devaru, Dayakar; Maddula, Ramakrishna; Gopalakrishnan, Bhaskaran
Quantity of energy required to produce a unit of product or specific energy consumption (SEC) is an important aspect to lumber producing sawmills since it can also represent production efficiency to some extent. The current research focuses on establishing SEC profiles for hardwood lumber sawing in sawmills and comparing them with SEC of other sawmills. Benchmarking energy consumption will help the sawmill industry to know where it stands against industrial bests and realise how to improve their energy efficiency and productivity. SEC was calculated in the traditional way initially by taking total energy consumption from energy bills and dividing it by total board feet sawn. Sawmills produced different lumber sizes which affected energy consumption and hence a method based on surface area cut was developed to calculate SEC. Better results were obtained by SEC calculated based on surface area cut since it exposed production bottle necks than traditionally calculated SEC.